PENGARUH SYSTEMATIC ORAL CARE DENGAN MADU TERHADAP DISFUNGSI RONGGA MULUT AKIBAT KEMOTERAPI PADA ANAK USIA 3-12 TAHUN - Sutari, Gusti Ayu Anik (Coping: Community of Publishing in Nursing, 2014)
Mouth cavity dysfunction is one of the side effects of chemotherapy. Most of the children who is taking chemotherapy will experience mouth cavity dysfunction. If this case is not being handled sooner, it will result on the dysfunction of nutrient balance which will result on the decrease of life quality of the children who suffer from cancer. One solution which is recommended to handle mouth cavity dysfunction nowadays is using oral care with honey. This study was aimed at investigating the effect of systematic oral care with honey toward mouth cavity dysfunction caused by chemotherapy on children of 3-12 years. This study is pre- experimental study (one group pre – test dan post- test design without control group). The sample of this study consists of 24 children with the age among 3-12 years old, in which the sample was gained through total sampling. The data of mouth cavity dysfunction employed Beck Oral Assessment Scale. All of the respondents were given systematic oral care with honey based on five days BOAS. The result of the study shows that there was a difference on the average decline of the score of mouth cavity dysfunction before and after the systematic oral care with honey was given. Before the treatment, the average score of mouth cavity disorder was 13.17, and after the treatment was given, the average score of mouth cavity disorder was 8.67. Based on the result of statistics Dependent “t” test, it was gained that the score of  p =0.000, meaning that p<a (0.05). It can be concluded that there is an effect of systematic oral care with honey toward moth cavity dysfunction resulted from chemotherapy on children of 3-12 years.
Keywords: Honey; Systematic Oral Care; Chemotherapy; Mouth Cavity Dysfunction